الجملة الفاعلیة بین البصریین والكوفیین - م.د. غانم عودة شرھان السوداني (College of Education for Women, 2019)
After the tiring search in sources about this major. I agree with Cofians about Possibility of the subjects comes clause else it comes phrase in many position I mentioned it in evidences . there clear proof the verb comes objective of clause if it uninflected, it will come subject of the passive. else it mention in previous evidences. also genestive clause comes subject of the passive if it the subject comes uninflected with the presence the object . It is clear in the language of Roba s poetry which it is mentioned in the search and others .